Properties controlling the bend-assisted fracture of AHSS. (December 2015) - Lee, J.; Kim, J.H.; Lee, M.G.; Barlat, F.; Zhou, C.; Chen, Z.; Wagoner, R.H.
Abstract: Bend-assisted fracture, also commonly called shear fracture, is the splitting of metal sheets during forming in tight-bending regions. It has been shown to be predominantly a result of plastic localization for most advanced high strength steels (AHSS). Such fractures are poorly predicted by typical industrial methods involving finite element modeling (FEM) and forming limit diagrams (FLDs). In order to understand the source of the problem, the sensitivity of simulated shear-fracture formability to material and process parameters was determined using FEM in conjunction with a realistic range of constitutive models, element sizes, and friction coefficients. Two types of shear fracture process were simulated. (1) Draw-bend fracture (DBF) tests are laboratory analogs of industrial forming conditions producing shear fracture; they offer the opportunity of experimental validation but introduce complexity because of varying strain state and unavoidable transitions between shear fracture and tensile fracture. (2) Plane-strain (PS) draw-bend fracture simulations correspond more closely to industrial forming conditions; they simplify the modeling (fixed strain state, no transitions) but no corresponding full-scale laboratory experiments currently exist. The DBF test was found to be sensitive to every material and process parameter tested, with the largest factors being the form of 1-D hardening law and the yield function. Varying these quantities in ranges representing what practical measurements would produce showed variations in predicted formability of up to 80%. The PS simulations, which represent industrial practice more closely, showed large variations in predicted formability only for two variables: 1-D hardening law and friction coefficient. All other parameters were insignificant, except for thermo-mechanical effects, which were important for high-rate tests only. These results show why it is difficult or impossible to predict shear fracture using standard industrial techniques designed for traditional steels. They suggest ways to modify such techniques to accommodate advanced high strength steels. The results also give guidance to alloy designers in terms of which constitutive parameters are most important in inhibiting shear fracture, and which are relatively insignificant. Highlights: Shear fracture is controlled primarily by strain hardening and friction. At high rates, thermo-mechanical effects are of modest importance. Common industrial techniques (low-rate, isothermal tests low curvature FLD's) cannot predict shear fracture.